A commentary on James - Spencer, Aída Besançon 1947- (Grand Rapids, MI Kregel Academic, 2020)
This definitive commentary sheds exegetical and theological light on the book of James for contemporary preachers and students of Scripture. Listening closely to the text while interacting with the best of scholarship, Aida Besancon Spencer shows what this epistle meant for the early church and what it means for us today. In addition to its perceptive comments on the biblical text, this volume examines James's four key themes: speaking wisely, using wealth, persevering in trials, and becoming doers of the Word. Spencer offers astute guidance to preachers and teachers wanting to do a series on James, with homiletical trajectories for each passage to show how historical narrative can be presented from the pulpit and in the classroom. --
Includes bibliographic references (pages 311-320)
Keywords: Bible -- Commentaries; Bible -- Criticism, interpretation, etc; Bible; Commentaries; Criticism, interpretation, etc